Why Allah, The Omnipotent, Omniscient, Omnipresent, and Omnibenevolent (also known as ‘The Supreme Lord of The Universal Committee and Divine Council’) Is Not Alleviating The Hardship and Agony of the Palestinian Muslims of Palestine? - Guru Dev Teeluckdharry (Formad English Foundation NTB Jakarta, 2025)
This study addresses the persistent humanitarian crisis faced by Palestinian Muslims under the oppression of the Zionist Government of Israel, marked by widespread killings, displacement, and the suffering of women and children. The central problem examined is the theological question of why Allah, described as Omnipotent, Omniscient, Omnipresent, and Omnibenevolent, has not yet alleviated the hardship and agony of the Palestinian people. The research aims to explore the divine attributes of Allah within the framework of Islamic theology while also engaging comparative references to broader Abrahamic traditions. Using a qualitative library research design, this study draws upon primary sources including the Qur’an, Hadith, and classical tafsīr, as well as secondary sources such as contemporary scholarly works and journal articles. Data collection was conducted through thematic review and organization of textual materials, while content analysis was applied to interpret the theological significance of Allah’s attributes, particularly the balance between mercy, justice, sternness, and divine tests. The results indicate that, while the suffering of the Palestinian Muslims can be understood as a divine test as mentioned in the Qur’an, it also reflects the broader reality of Allah’s attributes that include sternness and justice towards human ingratitude and disobedience. This dual perspective emphasizes the importance of patience, faith, and steadfastness, while also acknowledging divine wisdom that surpasses human comprehension. The conclusion highlights the need for Muslims to strengthen their belief in Allah’s comprehensive attributes, maintaining faith in His ultimate justice and mercy despite ongoing trials.